The eating behaviors and nutritional status of school teachers (One Health & Risk Management, 2023)
Introduction. There have been studies that have demonstrated the positive association between the incidence of diseases and irrational nutrition, which is characterized by serious violations of the diet, deficiency of vitamins, minerals, mainly calcium, magnesium, diets that do not meet regulatory requirements for content of the main food groups.The aim of this study was to investigate the association between eating behavior with nutritional status and body composition of high schools’ teachers.Material and methods. In order to achieve the proposed goal, a descriptive cross-sectional study was performed. Data collection was carried out in 2 stages. The first stage was the application of a structured questionnaire that was applied online. This questionnaire contains a total of 159 questions, of which 96 –determined the demographic grade and general clinical status,37 referred to the teachers' diet, 24 were organized in the form of a psychological questionnaire in which the respondents’ answers were appreciated on a scale with degrees from 0 to 5. The second stage was bioelectrical impedance analysis (BIA) of a sample using the TANITA BC730. The study sample consisted of 519 teachers, heads of departments and directors from a single school board, from the Republic of Moldova. Complex sample analyses were conducted using SPSS version 22.0 (IBM Corporation, Chicago, IL).Results. Women represented 97% of respondents from the primary schools and 89% – from the secondary schools. Average age was 46.6±3.77 years old. The work experience was 20.4±11.3 years. The majority of them were working in public schools (primary school – 4.6%; gymnasium – 52.2%, secondary schools – 43.2%) and 12.3% – in private schools. Most teachers were married (83.4%) and had in their custody on average 2 children (54.7%). Evaluating the body composition, the following data were obtained: teachers had an average height of 164.6±6.20cm; body mass – 67.9±14.2 kg; the share of body fat-28.4±8.87%; the muscle mass – 45.6±8.5kg; the bone mass – 2.4±0.42 kg; the BMI – 24.9±4.28; body water percentage – 52.3±5.89%; the metabolic age – 40±12.6 years; the daily energy requirement – 2370.2±455.11 kcal. More than 25.8±6.25% eat 2 times a day and more than 28.9±4.89% don't keep track. Around 46.0±9.57% claimed that they do not eat healthy and 37.6±12.09% said that they do not eat according to their age. Using Segmental body composition monitor model, we obtained that in 36.4±11.23% teachers have a subnormal constitutional and normal aesthetic type, 27.3±7.25% developed an overweight constitutional type and 9.1±0.25% – obese. More than 90.9±15.92% of teachers were at risk of developing osteoporosis.Conclusions. The health-saving behavior of teachers in relation to food was not formed. Teachers' awareness of the requirements of a healthy diet is insufficient, superficial, as a result, but also due to lack of time and, as the respondents admit, "laziness", with a sufficiently high motivation of teachers to improve their nutrition. Identified nutritional disorders affect the health and nutritional status of teachers.
Keywords: real nutrition; eating behavior; nutritional status; healthy lifestyle; high school teachers